2018
DOI: 10.1017/s0305004118000014
|View full text |Cite
|
Sign up to set email alerts
|

On Diophantine transference principles

Abstract: Abstract. We provide an extension of the transference results of Beresnevich and Velani connecting homogeneous and inhomogeneous Diophantine approximation on manifolds and provide bounds for inhomogeneous Diophantine exponents of affine subspaces and their nondegenerate submanifolds.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…For real vectors and , this provides a lower bound for the uniform simultaneous inhomogeneous exponent in terms of the dual exponent . There have since been refinements and generalisations by a number of authors, among them Beresnevich and Velani [BV10], Ghosh and Marnat [GM19], and Chow et al [CGGMS].…”
Section: Diophantine Exponents and Transference Inequalitiesmentioning
confidence: 99%
“…For real vectors and , this provides a lower bound for the uniform simultaneous inhomogeneous exponent in terms of the dual exponent . There have since been refinements and generalisations by a number of authors, among them Beresnevich and Velani [BV10], Ghosh and Marnat [GM19], and Chow et al [CGGMS].…”
Section: Diophantine Exponents and Transference Inequalitiesmentioning
confidence: 99%
“…Corollaries 1 and 2 combined with (14) provide the following two results. A similar approach was used in [1,9] in the "nonweighted" case.…”
Section: Case Of One Linear Form and Marnat's Examplesmentioning
confidence: 99%
“…It is worth mentioned that in [19], it has been shown that the homogeneous to inhomogeneous transference principle of [8] is flexible enough to be used for arbitrary Diophantine exponents, not just the critical or "extremal" one. As demonstrated in [19], this naturally extends the scope of potential applications of the original transference principle.…”
Section: Remarksmentioning
confidence: 99%
“…It is worth mentioned that in [19], it has been shown that the homogeneous to inhomogeneous transference principle of [8] is flexible enough to be used for arbitrary Diophantine exponents, not just the critical or "extremal" one. As demonstrated in [19], this naturally extends the scope of potential applications of the original transference principle. Beyond extremal statements such as (1.7), the complete inhomogeneous version of the Khintchine-Groshev theorem, both convergence and divergence cases, for nondegenerate manifolds is established in [1].…”
Section: Remarksmentioning
confidence: 99%